Electromagnetic stirrer and use method thereof - FENG ZHAN; YOU ARAM; ZHU QIONG; QIU LIWEN; LI HEWEN; HU MING; QIU YA; LU KAIYANG; YU YANGCHAO (2022)
The invention belongs to the technical field of electromagnetic stirrers, and particularly relates to an electromagnetic stirrer and a using method thereof. A magnetic mechanism; the automatic rod taking mechanism is detachably arranged at the middle position of the back surface of the base; the magnetic stirring rod is attracted to the bottom of the automatic rod taking mechanism through magnetic force, the automatic rod taking mechanism is used for taking and placing the magnetic stirring rod, and the magnetic mechanism attracts the center position of the magnetic stirring rod through magnetic force and is used for improving the stability of the magnetic stirring rod during autorotation; according to the magnetic stirring device, the rotating electromagnet and the cylindrical magnetic block are arranged, when the magnetic stirring rod is subjected to large resistance or uneven acting force during rotation, the cylindrical magnetic block and the rotating electromagnet can attract each other, the magnetic sti